2015
DOI: 10.4097/kjae.2015.68.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia for permanent spinal cord stimulation with a cylindrical type lead: a case series

Abstract: Spinal cord stimulation (SCS) in trials involving external stimulation are easily conducted under local anesthesia. However, implantation of a permanent SCS system is painful, and can be intolerable in some patients. Epidural anesthesia can be used to perform the SCS implantation without discomfort if the patient can localize the area of paresthesia. However, little is known about epidural anesthesia for SCS. This paper reports 23 cases of permanent SCS with a cylindrical type lead implanted under the epidural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Local anesthesia spread to the epidural space is generally considered to result in insufficient or inadequate paresthesia. However, Lee et al (16) demonstrated the successful use of epidural anesthesia in SCS implantation without disturbing perception or affecting paresthesia. In this case report, 1% lidocaine (~10 mL) was used to infiltrate at the subcutaneous skin.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthesia spread to the epidural space is generally considered to result in insufficient or inadequate paresthesia. However, Lee et al (16) demonstrated the successful use of epidural anesthesia in SCS implantation without disturbing perception or affecting paresthesia. In this case report, 1% lidocaine (~10 mL) was used to infiltrate at the subcutaneous skin.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous issue of the Korean journal of anesthesiology , Lee et al [ 7 ] described the pain management during a procedure for permanent spinal cord stimulation with a cylindrical type lead insertion. They mentioned that implantation of a permanent SCS system is painful and intolerable in some patients.…”
mentioning
confidence: 99%